The Improvement of Cardiac and Endothelial Functions of Xue-Fu-Zhu-Yu Decoction for Patients with Acute Coronary Syndrome: A Meta-Analysis of Randomized Controlled Trials. (10th February 2022) - Chen, Shiqi; Wu, Xiaoxiao; Li, Tong; Cheng, Weiting; Han, Xiaowan; Li, Yang; Wang, Baofu; Teng, Yu; Zhao, Mingjing; Wang, Yahong
Abstract : Background . Xue-Fu-Zhu-Yu decoction (XFZYD) is a traditional Chinese prescription that has been used to treat patients with blood stasis in China for many years. The present study aimed to evaluate the improvement of cardiac and endothelial functions of XFZYD for patients with acute coronary syndrome (ACS) through a systematic review and meta-analysis. Methods . Six databases were searched to collect RCTs related to the treatment of XFZYD for ACS. The primary outcomes were cardiac and endothelial functions, including the levels of left ventricular ejection fraction (LVEF), left ventricular end-diastolic diameter (LVEDD), and left ventricular end-systolic diameter (LVESD) in echocardiography, as well as the changes in the levels of nitric oxide (NO), endothelin-1 (ET-1), intercellular adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1) in the serum. The secondary outcomes were the blood levels of oxidative damage markers (including superoxide dismutase (SOD) and malondialdehyde (MDA)), C-reactive protein (CRP), brain natriuretic peptide (BNP), creatine kinase-MB (CK-MB), and cardiac troponin I (cTnI) as well as the incidence of adverse drug reactions (ADRs). Weighted mean difference (WMD) was estimated for all the outcomes with the random effects model. This type of analysis was conducted in the subgroups of the ACS subtypes, and the methodological quality was assessed using the handbook of Cochrane Collaboration. Results . A total of 1, 658 records were identified, and 16 randomized controlled trials (1, 171 patients) were included. The primary outcomes suggested that XFZYD combined with routine treatment improved LVEF, reduced LVEDD and LVESD, and also improved the serum levels of NO, and reduced the levels of ET-1 and ICAM-1. XFZYD combination therapy significantly ameliorated the blood levels of SOD, MDA, BNP, CK-MB, and cTnI. However, the results indicated no significant difference between XFZYD plus routine treatment and routine treatment for the levels of VCAM-1 and CRP. Moreover, all the ADRs reported in the included studies were slight and the patients recovered soon. Conclusions . The present study suggested that XFZYD may improve the cardiac and endothelial functions of ACS patients without serious ADRs. However, based on the mediocre methodological quality, the aforementioned conclusion should be confirmed in a multicenter, large-scale, and accurately designed clinical trial.